Digital Content Surveillance and Freedom of Expression on Over The Top Platforms in Indonesia - Muhammad Faqih; Fikri Amiruddin Ihsani; Ellyda Retpitasari (Pancasila: Jurnal Keindonesiaan, 2026)
The development of information technology has led to the emergence of Over The Top (OTT) platforms as new spaces for public expression. In Indonesia, the government has implemented digital content monitoring mechanisms to prevent misuse of digital media, including the spread of hoaxes, hate speech, and radicalism. However, such surveillance raises concerns regarding potential violations of the right to freedom of expression as guaranteed by the constitution and international human rights instruments. This study aims to analyze digital content surveillance in Indonesia from the perspective of State Administrative Law and to examine the balance between the state’s role as a regulator and its obligation to protect human rights, particularly freedom of expression. This research employs a normative legal approach with qualitative methods, examining legislation, legal doctrines, court decisions, and administrative practices related to digital content monitoring through statutory, conceptual, case, and comparative approaches. Data are collected through a literature study of primary, secondary, and tertiary legal sources and analyzed systematically based on principles of state administrative law and international human rights standards. The findings indicate that current monitoring policies tend to be one-sided, lack public participation, and do not provide transparent and accountable mechanisms for administrative objections. Moreover, reliance on ministerial regulations as the legal basis is considered inadequate within the hierarchy of legal norms. Therefore, digital content surveillance policies should be reformed based on legality, proportionality, transparency, accountability, and respect for democratic rule of law and citizens’ digital rights.